Understanding 'asking styles' can help board with fundraising. Issue 396 (8th August 2022) - Unknown
Abstract : Nonprofit executive directors often complain that getting their board to help with fundraising is a major challenge. The fact is, many board members don't feel comfortable asking for money, they feel unprepared to do so, and their efforts often fail, leading to even greater anxiety about it.